Hyperthyroidism induced by paraneoplastic human chorionic gonadotropin (hCG) production from testicular tumours: a retrospective clinical and histopathological study - Julia Rohayem; Jan Idkowiak; Sebastian Huss; Thomas Balke; Hendrik Schürmann; Birthe Heitkötter; Joachim Wistuba; Angela Huebner (Endocrine Connections)
Human chorionic gonadotropin (hCG) has structural similarities with thyroid-stimulating hormone (TSH) and may stimulate TSH receptors at higher concentrations. During pregnancy, placental hCG causes TSH suppression, contributing to hyperemesis. However, in males, clinical manifestations caused by excess hCG are rare. Herein, we describe complications of life-threatening thyroid storm caused by paraneoplastic hCG secretion from testicular germ cell tumours (GCTs) and aim to identify high-risk groups through retrospective analysis in n = 20 males (aged 17–55 years) with testicular hCG-positive GCTs. Seven hCG-positive testicular GCTs were classified as seminoma, and 13 were classified as non-seminomatous GCTs (NSGCTs). In 3/7 males with seminomas (43%), serum β-hCG concentrations were mildly elevated (median: 0.3 U/L; range: 0.3–82.1 U/L). In contrast, β-hCG was increased in 12/13 (92%) males with a NSGCT (median: 71.1 U/L; range: 0.3–1,600,000 U/L). In 10/13 males with NSGCT (77%), we detected components of embryonal cell carcinoma (EC), and in 7/13 (54%), we detected components of a choriocarcinoma (ChC). TSH was suppressed with high free thyroxine levels in two cases with NSGCT and excessively elevated β-hCG concentrations, but there was no TSH suppression in a further case with high β-hCG. One patient with NSGCT and high β-hCG levels presented with thyroid storm and imminent decompensation refractory to anti-thyroid treatment, requiring a total thyroidectomy. In the second patient, anti-thyroid treatment was initiated shortly after the diagnosis, successfully normalizing hyperthyroxinaemia. In conclusion, paraneoplastic β-hCG production, occurring in NSGCTs with components of ECs or ChCs, is a rare cause of thyrotoxicosis. Early recognition and treatment are critical to prevent a life-threatening thyroid storm.